The impact of employee competencies management as part of the human capital on the intellectual capital implementing process = Analiza wpływu systemu zarządzania kompetencjami na wybrane elementy kapitału intelektualnego przedsiębiorstw - Prusak, Rafał (Zielona Góra: Faculty of Economics and Management Press)
Competencies of employees and competence management are elements fairly well described in the literature. A modern approach to these issues, however, must have a broader than traditional character. This follows the significant changes that took place in management sciences expressed by an increased role of intangible assets. Intellectual capital, its components, connections with enterprise resources and elements of the environment are an important aspects of the strategic considerations undertaken by management staff in modern enterprises.
Keywords: kompetencje pracowników; kapitał intelektualny; kapitał ludzki; workers competences; human capital; Intellectual capital